Synergistic enhancement of sunflower lubricant incorporated anti-wear Eichhornia crassipes and tertiary-butyl-hydroquinone (TBHQ) additives - Abdollah, Mohd Fadzli; Amiruddin, Hilmi; Opia, Anthony Chukwunonso; Abdul Hamid, Mohd Kameil; Mohd Zawawi, Fazila; Veza, Ibham (Hashemite University, 2023)
Due to the impending depletion of petroleum reserves and environmental worries, the creation of bio-lubricants is a compelling subject of research. With the use of tertiary butylhydroquinone (TBHQ) and Eichhornia crassipes carbon nanotubes (EC-CNTs), this work intends to create an effective sunflower oil-based bio-lubricant and analyze its tribological performance using a ball-on-disk tribo-meter. Different additive concentrations were blended to create the bio-lubricant. The tribological analysis was conducted in terms of coefficient of friction (COF), wear rate, wear scar diameter, surface roughness for different speed, load and temperature. The morphology shows good structures of the employed additives, TGA revealed good thermal resistance, FT-IR indicated good compatibility with needed functional groups. Under tribological test at 1500 rpm, inclusion of additives (SFO + 0.9wt.% EC-CNTs + 0.3wt.% TBHQ) demonstrated good enhancement on sunflower lubrication, thus showing COF and wear rate values of 0.058 and 13.5 10-9 mm3 .m-1 .N-1 against base sunflower COF and wear rate values of 0.074 and 15.5 *10-9 mm3 .m-1 .N-1. Under surface roughness, application of additives lowers the roughness on the lubricated surfaces (SFO + 0.9 wt.% EC-CNTs = 0.447 µm), (SFO + 0.3 wt.% TBHQ = 0.453 µm), thus shows smoothest when blended the two additives together (SFO + 0.9 wt.% EC-CNTs + 0.3 wt.% TBHQ = 0.244 µm), against base SFO value of 0.522 µm. The use of additives in SFO shows synergistic result via nano-lubricant tribo-film formation resulting in commended outcome in all the conditions tested.